Defect-related visible luminescence of ZnO nanorods annealed in oxygen ambient - 蔡井维 徐建萍 张晓松 牛喜平 邢彤焱 季婷 李岚 (Optoelectronics letters, 2012)
ZnO nanorods prepared by a solution-phase method are annealed at different temperatures in oxygen ambient. The luminescence properties of the samples are investigated. In the same excitation condition, the photoluminescence （PL） spectra of all samples show an ultraviolet （UV） emission and a broad strong visible emission band. The asymmetric visible emission band of annealed samples has a red-shift as the annealing temperature increasing from 200 ℃ to 600℃ and it can be deconvoluted into two subband emissions centered at 535 nm （green emission） and 611 nm （orange-red emission） by Gaussian-fitting analysis. Analyses of PL excitation （PLE） spectra and PL spectra at different excitation wavelengths reveal that the green emission and the orange-red emission have a uniform initial state, which can be attributed to the electron transition from Zn interstitial （Zni） to oxygen vacancy （Vo） and oxygen interstitial （Oi）, respectively.